Actocardiogram : analysis of fetal motion and heart rate - Maeda, Kazuo (Jaypee Brothers Medical Publisers, 2016)
Actocardiogram (ACG) records fetal heart rate, direct fetal movements and uterine contractions using simple probes attached on the pregnant abdomen, and recorded on a moving chart. The same diagnosis is achieved as common cardiotocography (CTG), while fetal heart rate increases parallel to fetal movement, and unsolved problems in the CTG was solved by ACG, e.g. benign physiologic sinusoidal heart rate is diagnosed by cyclically changing fetal movements. Fetal hypoxia progresses according to changing ACG till severe fetal brain damage in the loss of fetal heart rate (FHR) variability. Fetal short-and long-term outcomes are diagnosed using the ratio of fetal heart rate acceleration duration to the fetal movement bursts duration. Fetal behaviour is decided using ACG parameter values. The "Actocardiogram" book details these advantages.